Pulmonary involvement for patients with Rheumatoid Arthritis: Spirometric study - Hameed Al-Tayyar, Ahmed S.; Mohammed, Najeeb H.; Jasim, Nizar A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Pulmonary involvement in patients with Rheumatoid Arthritis (RA) is a serious extra articular manifestation. Patients and Methods: 82 patients with RA and 40 control subjects were included in this prospective study. They were submitted to medical history, physical measurements (height, weight and BMI) and spirometric evaluation for FVC, FEV1, FEV1%, PEFR and FMF (FEF25-75%).Objective: The aim of the study is to detect pulmonary involvement, classify the type of involvement (whether obstructive, restrictive or mixed), and to find out whether pulmonary system was involved in the early stage of the disease and is asymptomatic and to determine the associated possible risk factors. Results: 42 patients with RA (51%) show abnormal spirometric results, mostly in the form of respiratory restriction in 33 patients (40%), obstructive results in 7 patients (9%); while mixed abnormality in 2 patients (2%). Various risk factors are correlated with reduced spirometric results.Asymptomatic patients with abnormal spirometry found in 9 (11%) and 6 patients (7%) had abnormal results within two years of their articular disease. Conclusion: Pulmonary involvement is common in Iraqi patients with RA, mostly in the form of respiratory restriction. Pulmonary involvement is believed to be asymptomatic in some patients and even occurs early in the disease process. Various risk factors are found to be correlated with the abnormal spirometry.